Characterization of Ni catalyst supported on α-Al2O3 and SiO2 for syngas production via dry reforming of glycerol - Norazimah, Harun; Sumaiya, Zainal Abidin; Nur Nabillah, Mohd Arif; Nurul Aini, Razali; Mohammad Tazli, Azizan (Dept. of Chemistry, UTM, 2018)
Ni-based catalysts supported on α-Al2O3 and SiO2 were prepared through wet impregnation method for glycerol dry reforming to produce hydrogen, carbon monoxide and methane. Glycerol dry reforming was carried out in tubular reactor at 973 K under atmospheric pressure. The catalysts were characterized using X-Ray Diffraction, Bruneuer-Emmet Teller surface area, Thermogravimetric Analysis, temperature-programmed reduction and Scanning Electron Microscopy. Ni/Al2O3 gives the higher glycerol conversion and hydrogen yield (14.46% and 9.82% respectively) compared to Ni/SiO2. This result was due to smaller crystallite size and higher specific surface area of Ni/Al2O3 compared to Ni/SiO2. Additionally, the nature of Al2O3 could increase metal dispersion as well as avoid the carbon deposition, helps the activity and the stability of this catalyst. The deposition of encapsulated carbon and filamentous carbon could be observed on Ni/Al2O3 and Ni/SiO2, respectively, and can be easily removed through oxidation.